Body and symbolism in organ donation - An introduction - Fernandes, Viviane (Brazilian Journal of Transplantation, 2014)
Thinking about organ donation is inseparable from the understanding of what is the body for the society from which one thinks, since the body is a symbol of the society, reflecting its social-cultural inconsistencies. Organ donation is linked to a set of meanings that arouses feelings that drive human action and legitimate them. Thinking about it allows the understanding and reflection on our own body and the positioning on such matter. It is important to the body’s reframing potential, death, and life within the context of the organ donation.